2005
DOI: 10.1029/2005jd005763
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cycle of tropical precipitation in Tropical Rainfall Measuring Mission (TRMM) satellite and ocean buoy rain gauge data

Abstract: [1] The climatological diurnal cycle of precipitation in the tropics is analyzed using data from rain gauges on ocean buoys and satellite measurements by the Tropical Rainfall Measuring Mission (TRMM) satellite. The ocean buoy data are from the NOAA/Pacific Marine Environmental Laboratory Tropical Atmosphere-Ocean/Triangle Trans-Ocean buoy Network in the tropical Pacific Ocean. TRMM data are from the precipitation radar (PR) and the TRMM microwave imager (TMI). Climatological hourly mean precipitation rates ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 42 publications
3
70
0
Order By: Relevance
“…Using the precipitation data from TRMM (Tropical Rainfall Measuring Mission) satellite, Nesbitt and Zipser [3] found that over oceans, the diurnal cycle of rainfall has a small amplitude and the maximum contribution to total rainfall from meso-scale convective E-mail: baiaj@ieecas.cn systems appears in the early morning, but land areas have a more significant diurnal cycle than oceans, with a minimum in the mid-morning and a maximum in the afternoon. Using the buoys data on oceans Bowman et al [5] confirmed the foregoing conclusions [2,3] .…”
Section: Introductionsupporting
confidence: 71%
“…Using the precipitation data from TRMM (Tropical Rainfall Measuring Mission) satellite, Nesbitt and Zipser [3] found that over oceans, the diurnal cycle of rainfall has a small amplitude and the maximum contribution to total rainfall from meso-scale convective E-mail: baiaj@ieecas.cn systems appears in the early morning, but land areas have a more significant diurnal cycle than oceans, with a minimum in the mid-morning and a maximum in the afternoon. Using the buoys data on oceans Bowman et al [5] confirmed the foregoing conclusions [2,3] .…”
Section: Introductionsupporting
confidence: 71%
“…Typically, the diurnal cycle of precipitation over the tropical open ocean is weak, with a peak before sunrise (Gray and Jacobson 1977;Bowman et al 2005). However, during periods of high solar radiation and weak winds, as well as a strong diurnal SST cycle, atmospheric convection over the ocean can behave similarly to that over land, with a strong diurnal cycle, growth of cumulus congestus, and a precipitation maximum in the late evening (Johnson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To address the geographical inhomogeneity of sampling, these composite data counts for each cloud type are normalized by dividing convective and stratiform pixel count of a grid box by the total scan pixel count of that grid box and multiplying by 100 to get the percentage value of convective / stratiform fraction of that grid box. Since these phases are spread over nine years, the diurnal bias in the sampling is also another likely source of error (Negri et al, 2002 andBowman et al, 2005). We expect the benefits of having such a high-resolution dataset to outweigh the disadvantage of some statistical fluctuations since the horizontal gradients and temporal scale of precipitation over this region during the monsoon season, are probably much larger than the sampling errors (Anders et al, 2006;Romatschke and Houze, 2011).…”
Section: Trmm Dataset and Its Processingmentioning
confidence: 99%